EpCAM (CD326) finding its role in cancer - Baeuerle, P A (Nature Publishing Group, 2007)
Although epithelial cell adhesion/activating molecule (EpCAM/CD326) is one of the first tumour-associated antigens identified, it has never received the same level of attention as other target proteins for therapy of cancer. It is also striking that ever since its discovery in the late 1970s the actual contribution of EpCAM to carcinogenesis remained unexplored until very recently. With a First International Symposium on EpCAM Biology and Clinical Application this is now changing. Key topics discussed at the meeting were the frequency and level of EpCAM expression on various cancers and its prognostic potential, the role of EpCAM as an oncogenic signalling molecule for cancer cells, recent progress on EpCAM-directed immunotherapeutic approaches in clinical development and the interaction of EpCAM with other proteins, which may provide a basis for a therapeutic window and repression of its growth-promoting signalling in carcinoma. Future research on EpCAM may benefit from a unified nomenclature and more frequent exchange among those who have been working on this cancer target during the past 30 years and will do so in the future.